(untitled) (Journal of Human Sciences, 2026)
This study sheds light on the Chadian national resistance to the French occupation from the perspective of the philosophy of history. It reviews the views of some schools of historical philosophy on the historical cycle: the cycle of civilizational decline experienced by Chadian society during the French occupation, and the cycle of political fragmentation within the ruling entities of the Chadian sultanates at the time. The schools of historical philosophy, which we draw upon in this study, not only provide insights into these historical events and facts, but also help us develop an understanding of the reasons for the weakness of the resistance and its defeat by the occupiers. This research aims to conduct a scientific applied study of the philosophy of history and civilization on the Chadian national resistance, to achieve a comprehensive, holistic, and in-depth understanding of the French occupation of Chad. This study employs the historical, descriptive, and comparative method to describe the movements of the French occupier into Chad. It also briefly reviews the views of the schools of historical philosophy, applying them to the reality of Chadian society at the time, and comparing them to form a more comprehensive basis through which to explain the trajectory of political and social decline in Chadian society during the French occupation. Hence, The importance of the philosophy of history lies in its application to this important phase of Chad’s history, the stage of the French occupation and the resistance that stood up to it. This research aims to conduct a scientific applied study of the philosophy of history and civilization on the Chadian national resistance, to achieve a comprehensive, holistic and in-depth understanding of the French occupation of Chad, by attempting to answer these questions: When and how did the Chadian national resistance begin? How is the Chadian national resistance viewed in light of the philosophy of history? Can the various theories of the philosophy of history be employed on the nature of the resistance, or not? All of this can be discussed in this study, which addresses the topic of national resistance, theories of the philosophy of history, and the employment of these theories.